Rectenna for Radio Frequency Energy Harvesting: A Review (ELEKTRIKA- Journal of Electrical Engineering, 2024)
The emergence of wireless charging technology is also a topic of debate among consumers, fabricators, researchers, and academics. This paper focuses on the literature review of several works on the previous enhancement technique that effect the performance of antenna design with rectifying circuit (rectenna) for energy transfer system technology. Several techniques are applied on this microstrip antenna design work to enhance the antenna performance such as slot, parasitic element, fractal, antenna arrays and others. The parameters that are considered in this work are return loss, resonant frequency with bandwidth, gain and the antenna dimension.